2013
DOI: 10.1371/journal.pone.0081612
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Direct Renin Inhibition on Myocardial Fibrosis and Cardiac Fibroblast Function

Abstract: Myocardial fibrosis, a major pathophysiologic substrate of heart failure with preserved ejection fraction (HFPEF), is modulated by multiple pathways including the renin-angiotensin system. Direct renin inhibition is a promising anti-fibrotic therapy since it attenuates the pro-fibrotic effects of renin in addition to that of other effectors of the renin-angiotensin cascade. Here we show that the oral renin inhibitor aliskiren has direct effects on collagen metabolism in cardiac fibroblasts and prevented myocar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 39 publications
(46 reference statements)
1
21
0
Order By: Relevance
“…However Montes et al (2012) found that renin was able to induce the up-regulation of profibrotic molecules through an Ang II-independent pathway, since inhibition of Ang II by losartan or of angiotensin converting enzyme by captopril had a minimal or no effect on the renin-induced up-regulation of the fibrotic mediators TGF-␤1 and collagen. In other conditions as in non-hypertrophic mouse model of myocardial fibrosis, aliskiren prevented collagen deposition by cardiac fibroblasts (Zhi et al, 2013). This may explain the decrease in the myofibroblasts as detected by ␣SMA noticed in group IV of the current study.…”
Section: Discussionsupporting
confidence: 68%
“…However Montes et al (2012) found that renin was able to induce the up-regulation of profibrotic molecules through an Ang II-independent pathway, since inhibition of Ang II by losartan or of angiotensin converting enzyme by captopril had a minimal or no effect on the renin-induced up-regulation of the fibrotic mediators TGF-␤1 and collagen. In other conditions as in non-hypertrophic mouse model of myocardial fibrosis, aliskiren prevented collagen deposition by cardiac fibroblasts (Zhi et al, 2013). This may explain the decrease in the myofibroblasts as detected by ␣SMA noticed in group IV of the current study.…”
Section: Discussionsupporting
confidence: 68%
“…Then the medium, which mostly contained cardiomyocytes, was decanted, and the purified CFs were cultured in fresh DMEM containing 10% FBS. Before reagent treatment, cells were starved with serum-free medium for 24 h. After incubation with IMD 1–53 (10 −7 m ol/L) for 30 min, CFs were stimulated with Hcy (2 × 10 −4 m ol/L) for 24 h as described 12) .…”
Section: Methodsmentioning
confidence: 99%
“…Plasma Hcy level was closely relative to left ventricular myocardial hypertrophy and left ventricle mass fraction 8, 9) . In addition, Hcy led to several heart morphological alterations including myocardial fibrosis and myocardial hypertrophy in vivo and in vitro 7, 1012) .…”
Section: Introductionmentioning
confidence: 99%
“…In vitro, all components of the RAAS activate cardiac fibroblasts. Renin directly induces a pro-fibrotic program in cardiac fibroblasts (63). Angiotensin II activates AT1 receptors stimulating cardiac fibroblast proliferation and enhancing matrix protein synthesis (64), (65), (66).…”
Section: The Molecular Signals Regulating Obesity-associated Fibrosismentioning
confidence: 99%
“…Aldosterone enhances proliferation (69) and potently stimulates matrix protein synthesis in cardiac fibroblasts, while activating fibrogenic signaling in cardiomyocytes (70) and macrophages (71). In vivo, renin inhibition, ACE inhibition, AT1 blockade and aldosterone antagonism attenuate interstitial fibrosis in experimental models of myocardial infarction and of cardiac remodeling induced by pressure overload (72), (73), (74), (63), (75). …”
Section: The Molecular Signals Regulating Obesity-associated Fibrosismentioning
confidence: 99%